The Relationship Between Leg Length Discrepancy and Scoliosis in Children Aged 4-6 Years - Naufal, Adnan Faris; Pristianto, Arif; Dewangga, Mahendra Wahyu; Setiawan, Arif; Arifah, Izzatul; Susilo, Taufik Eko; Karyanto, Muhammad Dhaffa (Universitas Muhammadiyah Surakarta, 2024)
Introduction: Scoliosis is defined as the lateral curvature of the spine reaching an angle of 10 degrees or more on coronal radiographs when an individual is standing. According to data from the World Health Organization (WHO), around 3% of the global population is at risk of experiencing scoliosis, while in Indonesia, the prevalence of scoliosis ranges between 3% and 5%. Leg length discrepancy is a situation where the length of both lower extremities is unbalanced. Leg length discrepancy can lead to various issues in body posture, such as scoliosis. This study aims to investigate the relationship between scoliosis and leg length discrepancy in children aged 4-6 years. The degree of scoliosis was measured using a scoliometer, and leg length examination was conducted using a measuring tape. Methods: This study is a quantitative research with a cross-sectional research design. The sample size was 567, selected through purposive sampling based on inclusion, exclusion, and dropout criteria. Results: The results, obtained using the Nonparametric Correlation Test with the Spearman Rank Test, indicate the absence of a relationship between leg length discrepancy and scoliosis, with a p-value of 0.189 (p>0.05) and a correlation strength level of 0.055, meaning the correlation is very weak, and the direction of the relationship is positive or in the same direction. Conclusion: There is no relationship between leg length discrepancy and scoliosis in children aged 4-6 years.